Peranan Teknologi Inseminasi Buatan (IB) pada Produksi Sapi Potong di Indonesia - nFN Kusriatmi; Rina Oktaviani; Yusman Syaukat; Ali Said (Jurnal Agro Ekonomi, 2014)
EnglishAs a source of animal protein, beef has a strategic value in the Indonesian economy.  National beef production growth is slower than that of consumption. It leads to an increased import. Lower growth of national beef production is due to low productivity of beef cattle. One of steps to achieving beef self-sufficiency policy is beef cattle productivity improvement through optimizing artificial insemination (AI). This study aims to analyze the impact of technology improvements through increased application of AI dosage on the performance of beef cattle industry, the livestock subsector, and forecasting beef self-sufficiency achievement in Indonesia. This study utilized annual time series data from 1990 to 2011. The data were analysed using an econometric model with simultaneous equations. Parameters were estimated using a Two-Stage Least Squares (2SLS) method. Forecasting domestic beef production and demand uses the econometric models. Results of the study reveal that (a) increasing dosages of AI applications will increase domestic cattle population and beef production, lower domestic beef prices, increase national beef demand, as well as improve GDP and employment of livestock subsector, (b) technological improvements by increasing dosages of AI application will accelerate achievement of beef self-sufficiency in Indonesia.IndonesianSebagai salah satu sumber protein hewani, daging sapi mempunyai nilai strategis dalam perekonomian Indonesia. Pertumbuhan produksi daging sapi nasional relatif lebih lambat dibandingkan dengan pertumbuhan konsumsi sehingga impor daging sapi cenderung meningkat dari waktu ke waktu. Rendahnya pertumbuhan produksi daging sapi nasional sebagai akibat dari rendahnya tingkat produktivitas ternak sapi potong. Salah satu langkah dalam kebijakan swasembada daging sapi adalah peningkatan produktivitas ternak sapi potong melalui optimalisasi Inseminasi Buatan (IB) untuk mendorong pertumbuhan produksi daging sapi nasional. Penelitian ini bertujuan untuk menganalisis dampak perbaikan teknologi melalui peningkatan aplikasi dosis IB terhadap kinerja industri sapi potong, subsektor peternakan, serta proyeksi pencapaian swasembada daging sapi di Indonesia. Penelitian ini menggunakan data time series tahunan selama periode 1990-2011. Analisis data menggunakan model ekonometrik dengan sistem persamaan simultan. Estimasi parameter menggunakan metode Two Stage Least Squares (2SLS). Proyeksi produksi dan permintaan daging sapi domestik menggunakan model ekonometrik. Hasil analisis adalah sebagai berikut: 1) peningkatan aplikasi dosis IB akan meningkatkan produksi ternak sapi dan produksi daging sapi domestik, menurunkan harga daging sapi domestik, meningkatkan permintaan daging sapi nasional, serta meningkatkan PDB dan kesempatan kerja subsektor peternakan; dan 2) perbaikan teknologi melalui peningkatan aplikasi dosis IB akan mempercepat pencapaian swasembada daging sapi di Indonesia.